2014
DOI: 10.1603/an13036
|View full text |Cite
|
Sign up to set email alerts
|

Trapping Techniques for Siricids and their Parasitoids (Hymenoptera: Siricidae and Ibaliidae) in the Southeastern United States

Abstract: The recent introduction of Sirex noctilio F. (Hymenoptera: Siricidae) into North America has raised interest in native siricids and their parasitoids to better understand the potential impact of S. noctilio. In the southeastern United States, we assessed various techniques to capture native siricids and their parasitoids using traps, lures, and trap trees. During 2009–2011, in total, 2,434 wasps were caught including Eriotremex formosanus (Matsumura), Sirex nigricornis (F.), Tremex columba (L.), and Urocerus c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Other studies reported similar Þndings. In Louisiana, Barnes et al (2014) also found no differences between panel and multiple-funnel traps in the number of S. nigricornis caught. McIntosh et al (2001) found no difference among several trap types, including multiplefunnel traps, for capturing Siricidae in western Canada.…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…Other studies reported similar Þndings. In Louisiana, Barnes et al (2014) also found no differences between panel and multiple-funnel traps in the number of S. nigricornis caught. McIntosh et al (2001) found no difference among several trap types, including multiplefunnel traps, for capturing Siricidae in western Canada.…”
Section: Discussionmentioning
confidence: 78%
“…Bioassays conducted in controlled environments to test putative attractants or trap types are one way to circumvent this problem. Another is to conduct Þeld tests of trap and lure combinations with a closely related, but more common species, as we and others (Coyle et Barnes et al 2014) suggest that these locations are ideal for such studies. However, it is unknown whether S. nigricornis populations are generally greater in this region than further north, or locations chosen for trap placement were more attractive to wasps (i.e., near a lumber mill in Louisiana vs. an unthinned P. sylvestris plantation in Ontario).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations